2016
DOI: 10.1515/cclm-2015-0599
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of prostate cancer specific biomarkers PCA3 and ERG in whole urine, urinary sediments and exosomes

Abstract: This is the first study in which urinary PCa-specific biomarker levels were compared directly in three separate urine fractions. These results suggest that whole urine could be the urine substrate of choice for PCa-diagnostics based on analytical sensitivity, which is reflected directly in the high informative rate. Moreover, the significant positive effect of performing a DRE prior to urine sampling is confirmed. These findings could be of influence in the development of PCa-diagnostic urine tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 27 publications
(51 reference statements)
4
46
0
3
Order By: Relevance
“…Although the β-actin gene in one of the seventeen samples was not detected, this is in accordance with the results obtained from other enrichment methods [41], and therefore this may be related to the RNA content of the larger molecules in exosomes. Then exosmal miRNA maybe the more stable molecular for detection.…”
Section: Discussionsupporting
confidence: 90%
“…Although the β-actin gene in one of the seventeen samples was not detected, this is in accordance with the results obtained from other enrichment methods [41], and therefore this may be related to the RNA content of the larger molecules in exosomes. Then exosmal miRNA maybe the more stable molecular for detection.…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, the advantage to use whole urine samples as applied in the tests for PCA3 and TMPRSS2-ERG instead sediments is not only justified from the practical point of view but also with regard to the improved analytical sensitivity. On the other hand, biomarker levels measured in the three tested urine fractions in this study and presented in table 4 proved that there was a distinct difference between the levels in the whole urine and the sum of the two other fractions [6]. Thus, it can be concluded that a great amount of these mRNAs in the urine obviously occurs in free forms without any association to particles (exosomes) and without cellular confinement (sediments).…”
mentioning
confidence: 47%
“…While prostate-specific antigen (PSA) remains the basic parameter, the additional value of the two 2012 FDA-approved biomarkers prostate health index (PHI) in serum and prostate cancer gene 3 (PCA3) in urine has been confirmed numerous times [1]. The detection of TMPRSS2-ERG gene fusions in the tissue of approximately 50% of all prostate cancer patients and the subsequently developed urinary assay [2] put hope on further diagnostic improvement that could unfortunately only be partially fulfilled [3][4][5].The senior author of this article [6] in this issue of Clinical Chemistry and Laboratory Medicine played the key role in detecting PCA3 and developing urinary assays for PCA3 and TMPRSS2-ERG [7]. And this group is now the first that compared both markers in whole urine, urinary sediment and exosomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Набор Progensa предполагает анализ мо-чи без предварительной подготовки, ее забирают в среду, где проводят лизис клеток и сорбцию иссле-дуемых матричных РНК (мРНК) со специфичными олигонуклеотидами, иммобилизованными на магнит-ных шариках [8]. При другом подходе РНК выделяют из осадка мочи после центрифугирования [9], ряд ав-торов перед взятием мочи проводят массаж ПЖ в целях увеличения доли клеток из ПЖ в осадке мочи [10,11].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified